Lysozyme in Wine: An Overview of Current and Future Applications. Issue 5 (September 2014) - Liburdi, K.; Benucci, I.; Esti, M.
Abstract Lysozyme, a muramidase enzyme from egg whites (EC 3.2.1.17), is widely used in soluble form to control lactic acid bacteria in different foods. Moreover, hen egg white lysozyme is a hydrolytic enzyme that can be used to the control malolactic fermentation (MLF) during winemaking. MLF is only desirable in red and in some white wine, this suggest that MLF is at fault and needs to be controlled in all other types of wine. Lysozyme exhibits selective antimicrobial activity based on the hydrolysis of peptidoglycan cell wall constituents in lactic acid bacteria. In the last decade, several studies identified allergic reactions due to the presence of lysozyme in food. Given this relatively high incidence of lysozyme sensitization, and in accordance with the recently changed EC food legislation (1266/2010/CE), the use of lysozyme as an additive has to be declared on the ingredient label. To overcome this problem, the immobilization of the enzyme on insoluble supports, which allows the enzyme to be removed, has been the preferred strategy. In this context, this article offers a review of reports on lysozyme enological use over the last decade. It surveys the immobilization techniques and support materials used for lysozyme food preservation. This study attempts to provide useful guidance from the wealth of available immobilization data in the literature and, more importantly, to develop an integrated perspective on how to customize lysozyme for future enological uses.